PERKEMBANGAN SANGGAR SENI SEKAR MANIS DI KELURAHAN LINGGAJAYA KOTA TASIKMALAYA PADA TAHUN 1992-2016 - Ray Agung Maulana, - (2018)
This paper titled" Development of Sekar Manis Art Studio in Linggajaya, Tasikmalaya Regency From 1992 Until 2016". The research explain the development of Sekar Manis art studio in Tasikmalaya Regency. This study aims to explain about the development of Sekar Manis art studio, to limit the scope of research made 5 main problems, first how the background of the establishment, second how the role of managerial, third why can survive until 2016, the four factors hampering its development, and the fifth efforts of the government then the community to preserve it. Selection of Sekar Manis art studio as the object of research is based on the interest of the writer of Sekar Manis art studio which always exist to preserve Sundanese traditional arts in the midst of the rise of foreign cultures into Indonesia. In order to parse the problem the author examines it with historical method, which consists of four steps of heuristics, criticism, interpretation, and historiography. Based on the results of research that is First, about the background of the establishment of art gallery Sekar Manis. Established by Abah Momon who aspires to teach traditional Sundanese art to the young generation. Second, the role of the managers Sekar art studio there are some of the most prominent of the Abah Momon, Mrs. Rina and several other people. Third, there are two factors that make this studio survive to know 2016, namely external factors such as community appreciation and the development of the times and internal factors of art inheritance, facilities and infrastructure programs that support. Fourth, the inhibiting factors are funding problems and lack of faculty or trainers. Fifth, the efforts undertaken to preserve it involve the government of Tasikmalaya Regency, Linggajaya urban village and Cikurubuk community.:---